Foreign intervention in Africa : from the Cold War to the War on Terror - Schmidt, Elizabeth, 1955- (New approaches to African history ;, 2013)
Chronicles foreign political and military interventions in Africa from 1956 to 2010, helping readers understand the historical roots of Africa's problems.